A methodology for option pricing in electricity markets. Case study : Colombia (2016)
"Electricity is a commodity that behaves unlike others in the way that cannot be stored cheaply, its transport depends on existent electrical networks, and can be generated from different sources. This makes the price of electricity highly volatile. As a risk hedging strategy, different financial instruments have been developed, among them, options with electric energy as underlying. We developed a methodology for option pricing in electricity markets, taking into account multi seasonal behaviour. Future electricity prices estimation is presented for equatorial countries with similar climate conditions like hydro-dependent energy generation and tropical seasons (e.g. dry season, wet season), affected by El Niño Southern Oscillation. We made a descriptive analysis of the Colombian electricity market. Using mean reversion and mean-reverting jump diffusion models we made a forecast estimation of intra-day (Hourly) electricity prices based on historical spot data from Colombian electricity market..."